The art of economic persuasion : positive incentives and German economic diplomacy - Davis, Patricia A. (Patricia Annette), 1959- (Book collections on Project MUSE., 1999)
How the government and private interests in Germany cooperated to create friendly relations with Poland before the fall of communism.